The Level of Political Party Activity: Study of the Elections of Presidents in Cities with Poviat Rights of the Silesian Voivodeship in 2002-2018 - Kaczmarczyk, Karolina (Political Preferences, 2022)
Since 2002 in Poland voters in the local government elections can directly elect the head of the rural municipality, mayor and city president. Local elections, in Polish conditions, are treated as an arena favourable for local committees, often non-party. However, it should be noted that many analyses show that the higher the level of self-government, the more important the committees of political parties are. The increase in the participation of political parties in the election competition is also noticeable in medium and large cities. The author decided to check whether the cities with poviat status of the Silesian Voivodeship favour party committees or rather a committee unrelated to any political parties. For this purpose, the participation and effectiveness of these committees in local elections of cities presidents with poviat rights of the Silesian Voivodeship in 2002-2018 was analysed. The study confirmed that the level of politicization in elections is increasing, however, the effectiveness of party committees in the election of city presidents is lower than the effectiveness of local committees. In addition, political parties are more active and influential in larger cities.